Physicochemical and biological indicators in silages of taro (Colocasia esculenta (L.) Schott) tubers for animal feeding - Caicedo, Wiliam; Rodríguez, R.; Lezcano, P.; Ly, Julio; Valle, S.; Flores, L.; Ferreira, F. N. A. (Cuban Journal of Agricultural Science, 2016)
For assessing the physicochemical and biological indicators in silages of taro (Colocasia esculenta (L.) Schott) tubers for animal feeding, four silages with waste tubers were made. Treatments were: (1_NY) natural yogurt, (2_W) whey, (3_WMB5) whey and 5 %molasses B and 4_WMB10) whey and 10 % molasses B. The experimental design was a completely randomized of simple classification. Regarding the temperature at day zero, treatment2_W showed the highest value (P < 0.05) (22.65 ºC). At day one, 1_NY exhibited the highest value (P < 0.05) (22.53 ºC). At days two and three in treatment 2_W the highest values were obtained (P < 0.05) (22.53 – 22.49 ºC). From day four, to 180 in the 4_WMB10 the highest temperature was reached 22.83 – 22.54 ºC. Regarding pH, at day 0, treatment 3_WMB5 presented the highest value (P < 0.05) 5.4. From day 1 to 4, pH was proportionally reduced in the silages being higher in treatment 2_W, in 0.71 units from day 5 to 180. Later, the pH was stabilized in all silages. Treatment3_WMB5 showed the lowest value (P < 0.05) (3.93 – 3.83). Fungi, yeasts, total coliform and Escherichia coli were present on day zero and later were absent. There was no Clostridium spp. or Salmonella spp. throughout the study. The physicochemical and microbiological indicators in the silages until day 180 showed a perfect performance, fit for animal feeding.Key words: tubers, fermentation, microorganisms, animal feeding